INFLUENCE OF THE MARRAKESH AGREEMENT ON THE SYSTEM OF COPYRIGHT LAW - Markova, Marija (Teisė, 2015)
Article discusses Marrakesh Treaty to Facilitate Access to Published Works for Persons Who Are Blind, Visually Impaired or Otherwise Print Disabled, which was adopted by the World Intellectual Property Organization in 2013. Article analyses regulation of copyright exceptions at the international level and different national legal traditions dealing with this issue. The publication also focuses on several provisions of the Marrakesh agreement which future implementation at a national level potentially raises questions of their compatibility with the Bern Convention, other international agreements and Lithuanian law on Copyrights and Related rights. Article discusses provisions related to the exception from the right to translate, requirement for the “three step test” and commercial availability. Article concludes that the provisions related to the exception from right of translation must be interpreted in a narrow manner in order to maintain the separation of economic and moral rights of copyright holders. It also concludes that omission of the requirement for the commercial availability potentially fails to encourage copyright owners to adapt printed works for the needs of disabled people.